Firm Performance: Definition and Measurement Models - Omar Taouab; Zineb Issor (European Scientific Journal, ESJ, 2019)
The business environment of this new century has undertaken several changes, creating more and more complexity and uncertainty. In this changing environment, which characterizes the global economy today, firms face severe competitive pressure to do things better, faster, and low-priced. They need to cope with a growing number of challenges arising fromtheir environment, and also increase their ability to adapt. Nowadays, continuous performance is the objective of any firm. This is because it is only through performance that companies are able to experience development and make progress. Consequently, assessing and measuring business performance is of significant importance, since companies are constantly seeking effective and efficient results.